Competing with Superstars - Ammann, Manuel; Horsch, Philipp; Oesch, David (Management Science, 2016)
This paper investigates the effect of superstar chief executive officers (CEOs) on their competitors. Exploiting shocks to CEO status due to prestigious media awards, we document a significant positive stock market performance of competitors of superstar CEOs subsequent to the award. The effect is more pronounced for competitors who have not received an award themselves, who are geographically close to an award winner, and who are not entrenched. We observe an increase in risk taking, operating performance, and innovation activity of superstars’ competitors as potential channels for this positive performance. Our results suggest a positive overall welfare impact of corporate superstar systems due to the incentivizing effect on superstars’ competitors. This paper was accepted by Wei Jiang, finance.